2020
DOI: 10.7759/cureus.7125
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hiatal Hernia Repair in Patients with an Intrathoracic Pancreas: Case Series and a Review of Literature

Abstract: Transhiatal herniation of the pancreas is rare with only 17 cases reported in 25 years. Presentation of pancreatic herniation is diverse. In the majority of cases, the pancreatic herniation is found incidentally on CT-scans made for evaluating complaints related to a large or giant hiatal hernia. We present a literature review and case series of three patients with symptomatic type IV hiatal hernia with incidental, asymptomatic pancreatic herniation. All cases were managed laparoscopically with robotic assista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…But stretching of the transverse mesocolon due to increase in intra-abdominal pressure causes loosening of the posterior fascia resulting in pancreatic mobilization and herniation [7] . Pancreatic herniation is a rare occurrence, a review of the literature conducted in 2020, found 17 published cases of intrathoracic herniation of the pancreas [8] , [9] , with 12 cases occurring in or after the sixth decade of life, and with equal proportion of men and women [3] .…”
Section: Discussionmentioning
confidence: 99%
“…But stretching of the transverse mesocolon due to increase in intra-abdominal pressure causes loosening of the posterior fascia resulting in pancreatic mobilization and herniation [7] . Pancreatic herniation is a rare occurrence, a review of the literature conducted in 2020, found 17 published cases of intrathoracic herniation of the pancreas [8] , [9] , with 12 cases occurring in or after the sixth decade of life, and with equal proportion of men and women [3] .…”
Section: Discussionmentioning
confidence: 99%